Nutritional benefits from domatia inhabitants in an ant–plant interaction: interlopers do pay the rent. (10th March 2014) - Chanam, Joyshree; Sheshshayee, Madavalam Sreeman; Kasinathan, Srinivasan; Jagdeesh, Amaraja; Joshi, Kanchan A.; Borges, Renee M.; Kay, Adam
Summary How a symbiosis originates and is maintained are important evolutionary questions. Symbioses in myrmecophytes (plants providing nesting for ants) are believed to be maintained by protection and nutrients provided by specialist plant‐ants in exchange for nesting spaces (called domatia) and nourishment offered by ant‐plants. However, besides the benefits accrued from housing protective ants, the mechanisms contributing to the fitness advantages of bearing domatia have rarely been examined, especially because the domatia trait is usually constitutively expressed, and many myrmecophytes have obligate mutualisms with single ant species resulting in invariant conditions. In the unspecialized ant‐plant Humboldtia brunonis (Fabaceae) that offers extrafloral nectar to ants, only some plants produce domatia in the form of hollow internodes. These domatia have a self‐opening slit making them more prone to interlopers and are occupied mostly by non‐protective ants and other invertebrates, especially arboreal earthworms. The protection mutualism with ants is restricted in geographical extent, occurring only at a few sites in the southernmost part of this plant's range in the Western Ghats of India. We examined nutrient flux from domatia residents to the plant using stable isotopes. We found that between 9% (earthworms) and 17% (protective or non‐protective ants) of nitrogen of plant tissues nearest the domatium came from domatia inhabitants. Therefore, interlopers such as earthworms and non‐protective ants contributed positively to the nitrogen budget of localized plant modules of this understorey tree. 15N‐enriched feeding experiments with protective ants demonstrated that nutrients flowed from domatia inhabitants to nearby plant modules. Fruit set did not differ between paired hand‐pollinated inflorescences on domatia and non‐domatia bearing branches. This was possibly due to the nutrient flux from domatia to adjacent branches without domatia within localized modules. This study has demonstrated the nutritive role of non‐protective ants and non‐ant invertebrates, hitherto referred to as interlopers, in an unspecialized myrmecophyte. Our study suggests that even before the establishment of a specialized ant–plant protection mutualism, nutritional benefits conferred by domatia inhabitants can explain the fitness benefits of bearing domatia, and thus the maintenance of a trait that facilitates the establishment of a specialized ant–plant symbiosis.